Mental Lexicon and Dictionaries of Arabic Language for Non-Native Speakers - Hres, Maryia (LANGUAGE ART, 2021)
The paper studies mental lexicon, describes its main features and overviews existing theories of information distribution in mental lexicon of a monolingual and bilingual person. As well, it compares the structure of mental lexicon with that of a paper dictionary, and the mental lexicon of a native speaker of the Arabic language with that of a non-native speaker. The researcher hypothesizes that due to some differences in the structure of mental lexicon of native and non-native speakers some explanations of lexical entries used in dictionaries that target native speakers may not be relevant for dictionaries that aim at second language learners. In order to prove this hypothesis a study was held in Qatar University which embraced two groups of students: students of the Arabic language as a native language and those who learn Arabic as a second language.